Pemanfaatan Limbah Pertanian Dan Ternak Menjadi Pupuk Organik Dalam Pengembangan Sayuran, di Desa Cialam Jaya Kabupaten Konawe Selatan - Hijria; Syarni, Pertiwi (Amaliah: Jurnal Pengabdian Masyarakat, 2025)
n Cialam Jaya Village, South Konawe District, there are two large vegetable farming groups that manage vegetables from the people’s gardens, namely the Suka Maju Farmers and Binangkit Farmers groups. In addition, these two farmer groups on average have 2-3 cows. Agricultural waste in the form of unsold vegetables that every day from the two farmer groups produces an average of 12 kg of waste per day. The results of the waste harvested by vegetables and livestock belonging to the farmer group are left to be left in the field and in the cage. Vegetable crop cultivation has only relied on chemical fertilizers because they are easily available in local agricultural shops and the use of organic fertilizer in the cultivation of vegetable crops has never been applied in the cultivation of vegetables, but the problem is that the farmer group has not mastered the waste management system properly and environmentally friendly , do not master the processing of sewage into organic fertilizer appropriately and correctly, still using organic fertilizers (cow and chicken manure) that are still raw and not processed properly, still using chemical fertilizers that are not environmentally friendly, and do not understand the application of organic fertilizer as a product high economic value. The service program aims to provide solutions for vegetable farmer groups to minimize the use of chemical fertilizers and switch to using environmentally friendly organic fertilizers as well as being able to process agricultural waste and livestock into organic fertilizer in increasing vegetable crop production. The service program consists of three stages, namely socialization and counseling, training in the manufacture of agricultural waste and livestock into organic fertilizer, as well as evaluation of service activities. The program implementation time is for 1 month. The results obtained are awareness of farmers about the potential benefits of organic fertilizer for vegetable crops in Cialam Jaya Village, increasing farmers’ understanding of the manufacture of organic fertilizers from agricultural waste and livestock in increasing the yield of vegetable crops. The training program has been used directly by participants. The service team has compiled the module and conducted supervision by coordinating with the head of the farmer group to support the sustainability of the program. The evaluation results show that the process of activities has been going well but not all members of the farmer group are implementing the manufacture of agricultural waste and livestock into organic fertilizer.